Mesothelial cyst of the round ligament of the liver - Carboni, Fabio (J Minim Access Surg, 2016)
A 34-year-old man was admitted in our department with a 3 months history of epigastric pain, abdominal distension and tenderness. Helical computed tomography scan and magnetic resonance imaging showed a 10 cm low-density fluid-filled polilobate cystic lesion with internal septations and calcifications located between the left lobe of the liver, shorter gastric curvature, pancreas and mesocolon. Laparoscopic exploration was performed. Macroscopically the lesion was a unilocular serous cyst with a thick fibrous wall. Histopathology revealed a thin fibrous wall with a single layer of flattened to cuboidal mesothelial cell lining lacking any cellular atypia. The patient is currently alive without evidence of recurrence at 6 months. Cysts of mesothelial origin are rare lesions seen more frequently in young and middle-aged women, mostly benign and located in the mesenteries or omentum. Diagnosis is usually based on clinical examination and radiographic imaging. Immunohistochemistry is used to differentiate histologic type, with simple mesothelial cysts being positive for cytokeratins and calretinin and negative for CD31. The laparoscopic approach appears safe, feasible and less-invasive without compromising surgical principles and today should be considered the gold standard in most cases.